2008
DOI: 10.1017/s0022149x07874232
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between normocytic, hypochromic anaemia and iron concentration together with hepatic enzyme activities in cattle infected withFasciola hepatica

Abstract: Erythrograms determined from whole blood analyses and serum analyses for aspartate aminotransferase (AST), gamma-glutamyl transpeptidase (GGT) and alkaline phosphatase (ALP) activities, and iron concentration, were used in infected and uninfected cattle to determine the type of anaemia and degree of hepatic damage caused by Fasciola hepatica. Blood samples from 86 infected and 30 uninfected cattle were taken at slaughter. Haematological analyses revealed decreased levels of packed cell volume (PCV), haemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 14 publications
0
19
1
9
Order By: Relevance
“…Fasciolose crônica em bovinos jovens pode ocorrer eventualmente com sinais clínicos de emagrecimento, diarreia e edema submandibular e as perdas econômicas ocorrem, majoritariamente, devido a doença subclínica (Lotfollahzadeh et al 2008). Um surto de fasciolose aguda em vacas com cria ao pé criadas a campo foi descrito em área endêmica na região deste estudo (Adrien et al 2013).…”
Section: Discussionunclassified
“…Fasciolose crônica em bovinos jovens pode ocorrer eventualmente com sinais clínicos de emagrecimento, diarreia e edema submandibular e as perdas econômicas ocorrem, majoritariamente, devido a doença subclínica (Lotfollahzadeh et al 2008). Um surto de fasciolose aguda em vacas com cria ao pé criadas a campo foi descrito em área endêmica na região deste estudo (Adrien et al 2013).…”
Section: Discussionunclassified
“…The decrease in RBC counts can be due to decreased production or peripheral destruction of RBCs or blood loss from direct blood feeding by the flukes: Blood has been recovered from regurgitated caecal contents and from hemorrhage into the parenchyma, the bile ducts and the abdominal cavity as a result of activity of the fluke. 9,15,16 The decrease in Hb concentrations may be due to deficiencies in iron implicated in fasciolosis and is a factor interfering with the synthesis of hemoglobin. The reduction in RBC counts, Hb and PCV in bovine fascioliasis may attributed to extensive loss of blood into bile duct due to the large amounts of flukes present in the liver or the acute loss of blood caused by the flukes.…”
Section: Discussionmentioning
confidence: 99%
“…2, 16 The severe anemia may be attributed to a chronic liver inflammation, which causes erythrogenesis depression. [17][18][19] Similar results for RBC and PCV were observed in cattle, 20 while the results for RBC and Hb were similar to those reported in cattle 21 and in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Major lesions of D. dendriticum are detected only at necroptic examination of the liver, because even in heavy infections, clinical symptoms are not manifested (Otranto and Traversa 2002). The effects of fasciolosis on hematological and biochemical parameters in ruminants were studied more than dicrocoeliosis (Yang et al 1998;Lotfollahzadeh et al 2008;Zeinsteger et al 2011). Yang et al (1998 showed that the activity of plasma aspartate aminotransferase (AST), glutamate dehydrogenase (GLDH), and gamma-glutamyl transpeptidase (GGT) significantly elevated in water buffaloes with experimental subclinical fasciolosis.…”
Section: Introductionmentioning
confidence: 97%
“…Yang et al (1998 showed that the activity of plasma aspartate aminotransferase (AST), glutamate dehydrogenase (GLDH), and gamma-glutamyl transpeptidase (GGT) significantly elevated in water buffaloes with experimental subclinical fasciolosis. Lotfollahzadeh et al (2008) observed the increase activities of serum AST, GGT, and alkaline phosphatase (ALP) in cattle infected with Fasciola hepatica (F. hepatica). They believed that the increased activities of serum enzymes indicated chronic hepatic and bile duct injuries associated with chronic infection with F. hepatica.…”
Section: Introductionmentioning
confidence: 97%